Utilization Of Clover Plants For Economic Improvement Of Investa Dana Dollar Mandiri In Setro Village - Dewi Nuraini; Evianah; Hendra Prasetya (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Community Service in Setro Village aims to provide assistance and training on the use of clover plants in this advanced pandemic era. The implementation method is carried out by providing training and assistance in the practice of making various preparations with clover raw materials such as making peanut brittle, cilok and clover nuggets. Where the participants presented are PKK cadres and village officials who are expected to be able to share their knowledge with other communities so that they can also be used for entrepreneurship in order to be able to help improve the family economy in difficult times like today.